Biomonitoring by phytoplankton diversity and biovolume depth profile of the Pasak Jolasid Reservoir, Lopburi Province, Thailand - Yupin Phoondee (2020)
© 2019 Bio Tech System. The study of the distribution of phytoplankton diversity and biovolume by depth profile was carried out by sampling water obtained from Pasak Jolasid Reservoir, Lopburi Province, Thailand. The samples were collected between November 2009 to October 2010 at 2 meters depth intervals from the surface towards the bottom area of the reservoir with maximum depth. From obtained results, 220 species from 89 genera of phytoplankton belonging to 7 phyla were observed, which were Chlorophyta (44.75%), Euglenophyta (15.98%), Cyanophyta (15.53%), Bacillariophyta (15.07%), Chrysophyta (4.11%), Pyrrhophyta (4.11%), and Cryptophyta (0.46%), respectively. Findings demonstrated uniform distribution of phytoplankton at the water surface but showed specific distributions at the thermocline layer. Highest biovolume was observed at the water surface, which decreased with increasing water depth. The highest phytoplankton biovolume was found to be 108,132,447 mm3/m3 at a water depth of 4 meters followed by 2, 0, and 6 meters, and then a steady decrease in biovolume from 8 to 20 meters with the lowest value was observed at 22 meters depth. Differences in distribution among depth profiles were observed in terms of phytoplankton diversity, density, and biovolume. The results of this study can be used as reference database in the assessment of water quality for further conservation and utilization of the reservoir.